Climate Change Scepticism A Transnational Ecocritical Analysis - Garrard, Greg (Environmental Cultures, 2019)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Climate Change Scepticism is the first ecocritical study to examine the cultures and rhetoric of climate scepticism in the UK, Germany, the USA and France. Collaboratively written by leading scholars from Europe and North America, the book considers climate skeptical-texts as literature, teasing out differences and challenging stereotypes as a way of overcoming partisan political paralysis on the most important cultural debate of our time.